An agent-based architecture for dynamic service provisioning in 3G mobile communication networks. (8th October 2010) - Dou, C.; Chen, Y.P.
Mobile Agent Technology (MAT) has gained momentum in telecommunications, it allows for a more decentralised realisation of service control and management software by bringing control or management agents as close as possible to the mobile devices and/or the mobile users. This paper proposes a Mobile Agent (MA)-based architecture for dynamic service provisioning, which is a main characteristic of the Virtual Home Environment (VHE) concept, in 3G mobile networks. This paper has demonstrated the feasibility and the effectiveness of the proposed MA-based architecture for dynamic service provisioning in next generation mobile networks.